If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6n(7n + -8) = 0 Reorder the terms: -6n(-8 + 7n) = 0 (-8 * -6n + 7n * -6n) = 0 (48n + -42n2) = 0 Solving 48n + -42n2 = 0 Solving for variable 'n'. Factor out the Greatest Common Factor (GCF), '6n'. 6n(8 + -7n) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0Subproblem 2
Set the factor '(8 + -7n)' equal to zero and attempt to solve: Simplifying 8 + -7n = 0 Solving 8 + -7n = 0 Move all terms containing n to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -7n = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -7n = 0 + -8 -7n = 0 + -8 Combine like terms: 0 + -8 = -8 -7n = -8 Divide each side by '-7'. n = 1.142857143 Simplifying n = 1.142857143Solution
n = {0, 1.142857143}
| xa+b=3 | | 9n+5=18n-76 | | 3x+4+2x+6= | | j^2+26j=0 | | (10-R)+(20-D)+(20-R)=0 | | 21p+78=32p+12 | | 3/4k-11=2 | | k^2+21k+20=0 | | 7a-21=6a(a-2) | | (x-1)(5x+3)=(3x-8)(x-1) | | 3ln(5x+6)=20 | | g^2-21g+20=0 | | 7n+34=15n-86 | | 6n-3=11+2n | | 5x-2(x-3)=-8+5x-2 | | 3d-4=7d-60 | | 6x=-7x^2+9x+3 | | 3x*x-30x=360 | | 6k^2-49k+8=0 | | 0=t^3+-3t+4 | | C+R=10 | | 3.5-0.04x=1.54 | | 9a-4=2(a+3) | | 16x^2-0x-1=0 | | f(9a)=x+7 | | (10-R)+R+(20-R)=0 | | 4x+3+5x-2= | | 9x+10=6x+1 | | 75-9g=5(-4+29) | | Y^2+30y-400=0 | | -4.9t^2+15t+0.4=0 | | 39-[2c+4]=2[c+5]+c |